Análise dos gastos públicos em um município do Sul de Minas Gerais - Fonseca, Ruth Ribeiro da (2016)
The objective of this thesis is to understand and explain how resources raised by the municipality of Ijacy, Minas Gerais, Brazil, in the last 11 years were managed. More specifically, we sought to analyze how the accountability is conducted and how such expenses are controlled by society. For this, the public expenses of the municipality of Ijacy, from the period of 11 years (2005-2015), were studied, basing on the constitutional principles of Brazilian public administration; analyze the social control of public expenses in light of the New Public Service approach. The research methodology used is based on a quantitative-qualitative approach of a theoretical-empirical nature. Data collection was done by means of bibliographic research, secondary sources and document research. The results of this thesis revealed, when studying the accountability and transparency of the municipality of Ijacy, that there was a shortage of information regarding the collection and application of public resources, consequently, making it difficult for public choices and social control. The present thesis on the assumption that the transparency of the accounting data can contribute for the effectiveness of Public Governance. Thus, we suggest the development of an extension project for high school students with the theme “Understanding public accounts for the participation of all in municipal management”, showing the importance of accounting in the process of social control and widening of democracy. Therefore, this thesis contributes in the field of accounting and public administration, in addition to emphasizing that government expenses must be of knowledge to all citizens.